2021
DOI: 10.1111/all.14833
|View full text |Cite
|
Sign up to set email alerts
|

Immune changes beyond Th2 pathways during rapid multifood immunotherapy enabled with omalizumab

Abstract: Background: Multifood oral immunotherapy (mOIT) with adjunctive anti-IgE (omalizumab, XOLAIR ® ) treatment affords safe, effective, and rapid desensitization to multiple foods, although the specific immune mechanisms mediating this desensitization remain to be fully elucidated. Methods: Participants in our phase 2 mOIT trial (NCT02643862) received omalizumab from baseline to week 16 and mOIT from week 8 to week 36. We compared the immune profile of PBMCs and plasma taken at baseline, week 8, and week 36 using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
(73 reference statements)
1
16
0
Order By: Relevance
“…Despite this limitation, the study of peripheral peanut-reactive T cells during OIT has considerable translational value, as changes in the peripheral blood can be easily monitored in a clinical setting. Moreover, we and others have successfully identified clinically relevant responses in peanut-reactive T cells from peripheral blood during OIT ( 17 , 22 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this limitation, the study of peripheral peanut-reactive T cells during OIT has considerable translational value, as changes in the peripheral blood can be easily monitored in a clinical setting. Moreover, we and others have successfully identified clinically relevant responses in peanut-reactive T cells from peripheral blood during OIT ( 17 , 22 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies showed that omalizumab facilitated a faster achievement of higher OIT maintenance doses as compared to regular OIT (32,(65)(66)(67)(68)(69). Importantly, while omalizumab used as an adjuvant to OIT improved its safety and tolerability, it did not lead to higher efficacy (67), although larger studies are required on this topic (70). In this context, biologics intended to block other pathways of the Th2 immune response, such as dupilumab have begun to be explored in FA patients (71).…”
Section: Efficacy and Effectiveness -The Prosmentioning
confidence: 99%
“…Using Ara h 2 peptide‐MHCII dextramers, Wang et al showed increased TGFβ production in allergen‐specific Th cells 74 . Adjunctive anti‐IgE (omalizumab) treatment enables rapid multifood oral immunotherapy and has been shown to reduce circulating IL‐4+ peanut‐specific Th cells 75 . In addition, the frequencies of peanut‐specific CD8+ and TCRγδ+ T cells were reduced, 75 suggesting reduced capacity of these inflammatory cells to migrate to the gastrointestinal tract.…”
Section: Recent Advances In Allergen Immunotherapymentioning
confidence: 99%
“…58 treatment enables rapid multifood oral immunotherapy and has been shown to reduce circulating IL-4+ peanut-specific Th cells. 75 In addition, the frequencies of peanut-specific CD8+ and TCRγδ+ T cells were reduced, 75 suggesting reduced capacity of these inflammatory cells to migrate to the gastrointestinal tract.…”
Section: Recentadvan Ce Sinallerg En Immunother Apymentioning
confidence: 99%